Skin cancer: BCC, SCC, MM and KS (a term of 7 years in Loghman Hakim Hospital) - Rahmati Roodsar, Mohammad; Zali, Hakimeh (Archives of Advances in Biosciences, 2013)
Skin cancer has a broad and burdensome impact on the health and well-being of Iranian and account for substantial health care costs to the nation. The first most common form of skin cancer is basal cell carcinoma (BCC); followed by the squamous cell carcinoma (SCC) and the incidence of malignant melanoma (MM) is lower but is fatal. Kaposi sarcoma (KS) is a tumor caused by human herpes virus 8. In this study, prevalence and incidence of four skin cancer (BCC, SCC, MM and KS) was investigated by considering to risk factors include age, sex, skin color, sun exposure levels, Lesion location, occupations and timeout to seek treatment. In this study, 95 patients with skin cancers registered in Loghman Hakim hospital during the 7 years from 1998 to 2004 were analyzed. Result depicted that BCC is the most common skin cancer in both sexes and in all types male incidence was significant. Age prevalence of all was about 50 to 80 years. The most common sites of tumor involvement in BCC and SCC were head and neck; KS was lower limb and MM had sporadic lesions. Almost all of patients referred to diagnosis or treatment 1 to 5 years after the initial onset of the disease. Occupations of the majority of patients with skin cancer were farmers. More patients lived in the area with warm and dry climate. In sum up, the skin cancer risk factors are included older ages, residence of warm and dry regions, be male and farmer, and most importantly rate of exposure to sunlight can influence lifestyle of patients that everyone can easily take to protect in different ways.